Identification of resistance to stripe rust in 267 Chinese spring wheat landraces germplasm and molecular detection of disease resistance genes - Miaomiao Huang; Yuqing Zhang; Wanwei Hou; Ping Jin; Liang Huang (Biochemistry and Biophysics Reports)
Stripe rust (Puccinia striiformis f. sp. tritici) poses a major threat to Chinese wheat production. Assessing resistance levels and gene distribution in spring wheat landraces is critical for breeding durable resistant cultivars. This study evaluated 267 landraces from eight provinces for seedling resistance against dominant races CYR32/CYR34 and adult-plant resistance (APR) across five Qinghai natural disease nurseries during 2023–2024. At the seedling stage, 7.5 % (20 accessions; IT 0–6) and 12.4 % (33; IT 0–6) exhibited resistance to CYR32 and CYR34, respectively, with 2.99 % (8 accessions) conferring dual resistance. APR trials identified2.25 % (6 landraces) showed stable resistance, including Banjiemang with complete immunity (IT 0). Molecular analyses revealed prevalent Yr genes, Yr10 (38.6 %,103/267), Yr18 (29.6 %,79/267), Yr26 (20.9 %, 56/267) and multi-gene combinations 60 accessions (22.5 %) with 2 genes; 33 (12.4 %) with ≥3 genes. Notably, 97 accessions (36.3 %) lacked known Yr genes, suggesting novel resistance mechanisms. The Yr18/Yr26 combination emerged as a promising APR source. This study provides germplasm and genetic insights for pyramiding strategies to enhance stripe rust resistance.